Strategi Potensi Wisata Alam di Kampung Buantan Lestari - M Khori Kurnia Subagja; Andri Wibowo (IAI Nasional Laa Roiba Bogor, 2026)
This study aims to formulate development strategies for nature- and culture-based tourism in Buantan Lestari Village, Bunga Raya District, Siak Regency, Riau Province. Buantan Lestari Village possesses considerable natural resources and local wisdom; however, its tourism management has not yet been implemented optimally. This research employs a quantitative approach with a descriptive research design. Data were collected through the distribution of closed-ended questionnaires using a Likert scale to the residents of Buantan Lestari Village. The collected data were analyzed using descriptive statistical analysis and further examined through SWOT analysis by constructing the Internal Factor Analysis Summary (IFAS) and External Factor Analysis Summary (EFAS) matrices to determine the strategic position of tourism development. The results indicate that Buantan Lestari Village is positioned in the Weakness–Opportunity (WO) quadrant, suggesting the presence of significant external opportunities alongside various internal weaknesses. The main weaknesses identified include limited tourism facilities, low levels of community participation, minimal utilization of digital media for tourism promotion, and inadequate human resource capacity in the tourism sector. Based on this strategic position, the recommended strategy is a turn-around strategy, which focuses on overcoming internal weaknesses by leveraging available external opportunities. This strategy includes improving the quality of tourism supporting facilities, establishing and strengthening Tourism Awareness Groups (Kelompok Sadar Wisata/Pokdarwis), developing educational tourism packages based on local natural and cultural potentials, and optimizing digital promotion by involving the younger generation. The findings of this study are expected to serve as a reference for local governments and communities in formulating policies and programs for sustainable village tourism development and in contributing to the improvement of community welfare.